CLOCK Genetic Variations Are Associated With Age-Related Changes in Sleep Duration and Brain Volume. Issue 9 (15th December 2021) - Kim, Song E; Kim, Soriul; Kim, Hyeon-Jin; Kim, Regina Eun-Young; Kim, Sol-Ah; Shin, Chol; Lee, Hyang Woon
Abstract: Background: Although a connection between sleep disruption and brain aging has been documented, biological mechanisms need to be further clarified. Intriguingly, aging is associated with circadian rhythm and/or sleep dysfunction in a key gene regulating circadian rhythm, Circadian Locomotor Output Cycles Kaput (CLOCK), has been linked to both aging-related sleep disturbances and neurodegenerative diseases. This study aims to investigate how CLOCK genetic variation associates with sleep duration changes and/or volumetric brain alteration. Methods: This population-based cross-sectional study used data from the Korean Genome Epidemiology Study and analyzed sleep characteristics and genetic and brain imaging data in 2 221 participants (mean 58.8 ± 6.8 years, 50.2% male). Eleven single-nucleotide polymorphisms (SNPs) in CLOCK were analyzed using PLINK software v1.09 to test for their association with sleep duration and brain volume. Haplotype analysis was performed by using pair-wise linkage disequilibrium of CLOCK polymorphisms, and multivariate analysis of covariance was for statistical analysis. Results: Decreased sleep duration was associated with several SNPs in CLOCK intronic regions, with the highest significance for rs10002541 ( p = 1.58 × 10 −5 ). Five SNPs with the highest significance (rs10002541, rs6850524, rs4580704, rs3805151, rs3749474) revealed that CGTCT was the most prevalent. In the major CGTCT haplotype, decreased sleep duration over time was associated with lower cortical volumes predominantly in frontal and parietal regions. Less common haplotypes (GCCTC/CGTTC) had shorter sleep duration and more decreases in sleep duration over 8 years, which revealed smaller total and gray matter volumes, especially in frontal and temporal regions of the left hemisphere. Conclusion: CLOCK genetic variations could be involved in age-related sleep and brain volume changes.